Decoding Financial Performance: A 2023 DuPont Analysis of PT Asuransi Dayin Mitra Tbk and PT Asuransi Jasa Tania Tbk – A Comparative Perspective - Cahaya Putri Utama Zai; Dyah Palupiningtyas (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to analyze and compare the financial performance of PT Asuransi Dayin Mitra Tbk and PT Asuransi Jasa Tania Tbk in 2023 using the DuPont analysis method. The data used in this study are the financial statements of both companies for the year ended December 31, 2023. The analysis was conducted by calculating the net profit margin (NPM), total asset turnover (TATO), financial leverage (EM), and return on equity (ROE) of each company. The results indicate that PT Asuransi Dayin Mitra Tbk achieved better financial performance with an ROE of 5.66%, while the ROE of PT Asuransi Jasa Tania Tbk was only 1.24%. PT Asuransi Dayin Mitra Tbk outperformed in TATO and EM, whereas PT Asuransi Jasa Tania Tbk demonstrated a higher NPM. These findings provide practical implications for insurance company management and investors in decision-making processes. However, this study has limitations in terms of sample size, time period, and its focus on financial factors. Further research is needed to explore non-financial factors influencing the performance of insurance companies.